Managing External Volatility : Policy Frameworks in Non-Reserve Issuing Economies - Poirson, Helene (IMF Working Papers; Working Paper ;, 2020)
Since the global financial crisis, non-reserve-issuing economies (NREs) have been highly sensitive to episodes of external pressures. With monetary policy independence constrained by this sensitivity, many NREs have utilized other policy instruments. This paper confirms the vulnerability of NREs to external shocks and finds that in some circumstances managing such shocks with multiple instruments can both lessen the policy response required from any one policy tool to financial and external shocks and increase the effectiveness of policies in stabilizing macro-financial conditions. Effectiveness however does not always imply appropriateness, which rests on an evaluation of potential trade-offs and unintended consequences.